1987
DOI: 10.1007/bf01805761
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation needs and breast cancer: The first month after primary therapy

Abstract: Breast cancer is the most common neoplasm in occidental women, yet very little information is available about the rehabilitation needs of these patients. This report reviews in detail the physical, psychological, social, and financial problems identified by fifty women during the first month after primary surgical treatment. The most frequently reported problems were physical and psychological. Patients undergoing modified radical mastectomy (MRM) are compared with patients receiving segmental mastectomy and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 26 publications
3
34
1
3
Order By: Relevance
“…Similar to several previously-published studies, we observed that weight gain is a common problem in patients receiving adjuvant chemotherapy (Demark-Wahnefried et al, 1997;Demark-Wahnefried, Winer, & Rimer, 1993;Ganz et al, 1987;Goodwin et al, 1999;Heasman et al, 1985). Obesity is a known risk factor for the development of new cases of breast cancer and has been associated with decreased survival in active breast cancer patients (Protani et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to several previously-published studies, we observed that weight gain is a common problem in patients receiving adjuvant chemotherapy (Demark-Wahnefried et al, 1997;Demark-Wahnefried, Winer, & Rimer, 1993;Ganz et al, 1987;Goodwin et al, 1999;Heasman et al, 1985). Obesity is a known risk factor for the development of new cases of breast cancer and has been associated with decreased survival in active breast cancer patients (Protani et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Weight gain is a common problem among patients with breast cancer who receive adjuvant (post-operative) chemotherapy (Demark-Wahnefried et al, 1997;Demark-Wahnefried, Winer, & Rimer, 1993;Ganz et al, 1987;Goodwin et al, 1999;Heasman et al, 1985). This has been a consistent finding since the initial observation made by Dixon et al (1978).…”
Section: Introductionmentioning
confidence: 89%
“…The relationship of good body image with the resumption of sexual relations and sexual dysfunction is inconsistent. While the majority of studies have found this relationship (Carver et al, 1998;Beckmann et al, 1983;Steinberg et al, 1985;Pozo et al, 1992;Ganz et al, 2004;Yurek et al, 2000;Lee et al, 1992;Wolberg et al, 1989;Schain et al, 1994) a few have not (Ashcroft et al, 1985;Penman et al, 1986;Ganz et al, 1987;Goldberg et al, 1992).…”
Section: Body Image Sexuality and Sexual Problemsmentioning
confidence: 99%
“…Ancak yapılan çalışmalarda meme bütünlüğünün sağlanması, uzuv kaybı olmaması ve cinsel fonksiyonlarda kayıp yaşanmaması ile bu gibi durumların tolere edildiği ve hayat kalitesinin arttığı gösterilmiştir (13,14).…”
Section: Discussionunclassified